Parâmetros oftálmicos em espécimes de Cuniculus paca criadas em cativeiro - Balthazar da Silveira, Camila Pinho [UNESP] (2014)
Knowledge generated through specific studies is necessary for an approach about ophthalmic affections. Ophthalmic parameter variations may occur between species, specially regarding feral ones. Therefore, some ophthalmic parameters were studied in 13 Cuniculus paca individuals. Lacrimal production was quantified, corneal endothelium, intraocular pressure and also bacterial presence at the conjunctival microbiota were evaluated. Schirmer’s tear test, applanation tonometry and non-contact specular microscopy were employed in order to evaluate the variables. Conjunctival microbiota was evaluated through Brain Heart Infusion (BHI) culture and Polimerase Chain Reaction (PCR), so the presence of Staphylococcus aureus, Staphylococcus spp., Streptococcus spp. and Pseudomonas spp. microorganisms was investigated. Schirmer’s test I results were 4.10±0.44 mm/min, and there has been no significant difference between right and left eyes (p = 0.8275). IOP average range was 6.34 ± 0.43 mmHg, with no significant difference between right and left eyes (p= 0.9314). Ophthalmic examination revealed (blue/brown) pigmented bulbar conjunctiva, real eyelashes (only at superior eyelid), superior and inferior lacrimal points, brown iris, round pupil and nictitating membrane vestige. Anangiotic retinas were found. 100% of the individuals tested positive for Staphylococcus spp. and Streptococcus spp., 80% for Pseudomonas spp. and all of them tested negative for Staphylococcus aureus. Averages and standard errors, concerning corneal thickness were 0.353 ± 0.010 mm; regarding to area: 486.30 ± 9.56 μm2; referring to endothelial cells density: 2083.15 ± 42.47 cells/mm2; and relating to hexagonality: 67.07 ± 3.30%. The results obtained allow the conclusion that parameters set through this study might be used as reference to future ones, and also contribute to ophthalmopathy treatment and species preservation